Analisis Pengaruh PMDN Dan PMA Terhadap PDRB Jawa Timur - erika dwi fitriyani; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2022)
In essence, GRDP is the total increase in numbers received in all business sectors in the exclusive zone as well as the total number of goods and services most recently received in all economic units in the exclusive zone. The purpose of this research is to see the impact of domestic and foreign investment on GRDP in the East Java Region. The running test method used is quantitative research. The data source used is secondary data from BPS East Java. With time series data in the period 2011-2020. The results of multiple regression analysis show that the level of domestic and foreign investment has a significant effect on the level of GRDP in the East Java region